Use of Cangrelor as a Bridge to Left Ventricular Assist Device Implantation in a Patient with a Recent Drug‐Eluting Stent Who Developed Acute Tirofiban‐Related Thrombocytopenia. Issue 4 (4th March 2019) - Kabadi, Rajiv A.; Danelich, Ilya M.; Entwistle, John W.; Marhefka, Gregary D.; Reeves, Gordon; Boyle, Andrew J.; Qureshi, Ataul M.
Abstract : Current guidelines emphasize the need for at least 6–12 months of oral dual antiplatelet therapy consisting of aspirin and a P2Y12 inhibitor following drug‐eluting coronary artery stent implantation. In patients with recently implanted coronary artery stents who require urgent cardiac or noncardiac surgery, the benefits of maintaining oral dual antiplatelet therapy must be carefully weighed against the risks of excessive bleeding, and current practice is largely guided by individual surgeon preferences. When the effects of a second oral antiplatelet agent are undesirable during the perioperative period, the use of a short‐acting intravenous antiplatelet agent as "bridge" therapy that can be discontinued shortly before surgery is associated with a reduced occurrence of adverse clinical events in patients with recently implanted coronary stents requiring urgent coronary artery bypass graft surgery. Cangrelor is an intravenous adenosine triphosphate analog P2Y12 receptor antagonist with a short plasma half‐life that has been used off label in patients with recent coronary stents as a bridge to invasive procedures with excessive bleeding risk. To our knowledge, this is the first case report to demonstrate the safe and effective use of cangrelor as a bridge to left ventricular assist device implantation in a patient with a recently implanted drug‐eluting coronary artery stent who developed acute thrombocytopenia following reexposure to tirofiban, a glycoprotein IIb/IIIa inhibitor.